Susceptibilidade genética HLA-G e doença de Crohn em uma população do estado do Paraná - Leite, Carla Alessandra Ruiz (2013)
The combination of genetic and immunological mechanisms with gastrointestinal diseases indicates consistent relationships between these systems in both the pathophysiology of disease and in maintaining the health status of patients. The exact causes that lead to the development of Crohn's disease are unknown. Some genes related to the immune system have been identified as potential targets in the development of Crohn's disease. Among them is the HLA-G molecule which encodes an immunosuppressive role, with defense potential against inflammatory aggression and therefore decisive in balancing the immune response. The aim of this study was to evaluate the influence of HLA-G gene in the susceptibility / resistance in the development of Crohn's disease. The case-control study was conducted with 80 patients and 80 controls for exons 2 and 3 HLA-G and 99 patients and 323 controls for exon 8 of HLA-G. Genotyping was performed by molecular biology for genes HLA-G: exons 2 and 3 by PCR-SBT and exon 8 by PCR-SSP. Significant differences were found in exons 2 and 3 for the HLA-G*01:03 and HLA-G*01:04. The results of this project can contribute to the identification of disease markers and development of procedures that minimize their impacts for the individual and for the population, through proposals for the development of effective strategies for prevention, diagnosis and treatment.